Conflitos territoriais no processo de implantação da reserva extrativista (RESEX) do litoral sul de Sergipe - Araújo, Luís Ricardo Rodrigues de (2014)
The Extractive Reserve , which is evident by the law 9.985/2000 is an area of public domain to be used by traditional extractive populations whose livelihood is based on the extractivism and, additionally , on subsistence agriculture and breeding of small size, and has as objective protect the livelihoods and culture of these populations , and to ensure the sustainable use of natural resources unit ( BRAZIL , 2000) . Thus , to see this issue more closely , we chose this survey in the State of Sergipe , especially in the estuarine zone of Piauí and Fundo rivers , covering streams and fragile ecosystems of Municipalities Itaporanga D´Ajuda, Indiaroba and Santa Luzia Itanhy in whose areas is being made possible the possibility of creating and implementing the Extractive Reserve of the South Coast . Had as objective to evaluate conflicts of use / appropriation locked around the process of implementing the Extractive Reserve of the south coast of Sergipe . The methodological approach to structure the research in question was developed through analysis of landscape units . In order to characterize the social actors involved in the data collection procedure , the instruments of interviews and literature were used . For both , this search was structured through a qualitative and quantitative approach , guided by the analysis of landscape units . Finally , it is reiterated that this research did not seek the development of absolute truths but rather a scientific knowledge grounded in previously defined methodology. At the end of the research and preparation of this thesis, it was realized that the established territorial conflicts around the deployment process RESEX South Coast of Sergipe configures multiple territories that affect the social actors involved in the process from appropriation by actors social engaged in commercial activities, and social reappropriation of space by traditional communities. Produced and exposed results in this thesis can serve for the agents involved in the conflicts themselves as a material awareness and self-criticism , assisting in the search for ways to mediate conflicts .